COGNITIVE FUNCTIONS IN PATIENTS WITH ARTERIAL HYPERTENSION DEPENDING ON THE STATE OF HEMOSTASIS AND RENAL FUNCTION - Shmanko, Oleh (Journal of Education, Health and Sport, 2015)
Shmanko O. V. Когнітивні функції у хворих на артеріальну гіпертензію в залежності від стану згортальної системи крові та функції нирок = Cognitive functions in patients with arterial hypertension depending on the state of hemostasis and renal function. Journal of Education, Health and Sport. 2015;5(9):714-725. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.34428 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%289%29%3A714-725 https://pbn.nauka.gov.pl/works/674124 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.08.2015. Revised 05.09.2015. Accepted: 29.09.2015. УДК : 616.12-008.331.1-02: 612.115+612.46]-06:616.89-008.46 КОГНІТИВНІ ФУНКЦІЇ У ХВОРИХ НА АРТЕРІАЛЬНУ ГІПЕРТЕНЗІЮ В ЗАЛЕЖНОСТІ ВІД СТАНУ ЗГОРТАЛЬНОЇ СИСТЕМИ КРОВІ ТА ФУНКЦІЇ НИРОК COGNITIVE FUNCTIONS IN PATIENTS WITH ARTERIAL HYPERTENSION DEPENDING ON THE STATE OF HEMOSTASIS AND RENAL FUNCTION О. В. Шманько O. V. Shmanko ДВНЗ "Тернопільський державний медичний університет ім. І.Я. Горбачевського МОЗ України" Тернопіль, Україна Ternopil State Medical University Ternopil, Ukraine Summary. In 58 patients with arterial hypertension cognitive functions were examined depending on the state of hemostasis and renal function. The evaluation was conducted using short scale assessment of mental status (MMSE), Montreal scale (MOCA) for studying attention and concentration, executive functions, memory, language performance, constructive visual performance, abstract thinking, mental calculation, spatial and temporal orientation. The sustainability of attentional focus and speed of sensorimotor reactions were investigated using the tables of Schulte. The quality of life of patients was assessed for physical and mental components employing a questionnaire SF-12. It was found that such indicators of hemostasis system as international normalized ratio, prothrombin index, level of fibrinogen are diagnostic predictors of the risk of cognitive impairment development in patients with arterial hypertension, considering the results of neuropsychological assessment and evaluation of quality of life. No significant dependence was found between the glomerular filtration rate and the development of cognitive impairment in patients with arterial hypertension. Keywords: arterial hypertension, cognitive impairment, international normalized ratio, prothrombin index, fibrinogen, glomerular filtration rate. Резюме У 58 пацієнтів з артеріальною гіпертензією досліджено когнітивні функції в залежності від стану згортальної системи крові та функції нирок. Оцінку когнітивного статусу проводили за допомогою короткої шкали оцінки психічного статусу (MMSE), Монреальської шкали (MOCA) для вивчення уваги та концентрації, виконавчих функцій, пам’яті, мови, конструктивно-зорових навичок, абстрактного мислення, рахування та орієнтації. Стійкість уваги та швидкість сенсомоторних реакцій досліджували за таблицями Шульте. Оцінку якості життя пацієнтів з артеріальною гіпертензією за фізичним і психічним компонентом проводили за допомогою опитувальника SF-12. Встановлено, що показники коагулограми такі, як індекс міжнародного нормалізаційного відношення, протромбіновий індекс, рівень фібриногену є діагностичними предикторами ризику розвитку когнітивних порушень у хворих на артеріальну гіпертензію за результатами нейропсихологічного тестування та оцінки якості життя. Не виявлено значного взаємозв'язку між швидкістю клубочкової фільтрації та розвитком когнітивних порушень у хворих на артеріальну гіпертензію. Ключові слова: артеріальна гіпертензія, когнітивні розлади, міжнародне нормалізаційне співвідношення, протромбіновий індекс, фібриноген, швидкість клубочкової фільтрації.